Exploring stroke survivor and employer experiences of disruption within the RETurn to work After stroKE (RETAKE) trial during the COVID-19 pandemic - Trusson, Diane; Powers, Katie; Radford, Kate; Bowen, Audrey; Craven, Kristelle; Farrin, Amanda; McKevitt, Christopher; Murray, John; Phillips, Julie; Stevens, Judith; Clarke, David (Frontiers in Sociology, 2025)
IntroductionReturning to work is a goal for many stroke survivors, with benefits for individuals and society. The ReTurn to work After stroKE (RETAKE) trial, which aimed to improve stroke survivors’ work outcomes through early stroke-specific vocational rehabilitation (ESSVR), was ongoing during the COVID-19 pandemic. This study aimed to understand the impact of the pandemic on stroke survivors’ work ability and return-to work support.MethodsNine stroke survivors and five employers were interviewed. Thematic analysis informed by Normalisation Process Theory, found that biographical disruption experienced as a result of stroke was compounded by disruption on a global scale due to the pandemic.ResultsAttempts to mobilise resources in response to disruption were hampered by pandemic-related issues. Although returning to work offered continuity in pre-stroke identity, businesses were also disrupted by the pandemic. Findings suggest that returning to work was easier for stroke survivors able to work from home and those receiving ESSVR. The opportunity to work from home helped stroke survivors adapt to new ways of working necessitated by the impact of stroke and social distancing rules during the pandemic.DiscussionPost-pandemic, remote working is more acceptable, which may benefit future stroke survivors aiming to return to work whilst managing post-stroke fatigue. This may mitigate disruption to lives and post-stroke identities.